PENGARUH SETTING FISIK DAN AKTIVITAS PEDAGANG KAKI LIMA (PKL) TERHADAP LINKAGE KAWASAN Studi Kasus: Jl. Soeprapto, Jl. MT. Haryono, Jl. Raja Eyato dan Jl. S. Parman di Kawasan Perdagangan Kota Gorontalo - , FENDY FAIZAL GOBEL, Ir. T.Yoyok Wahyu Subroto, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Development of a corridor street involves many aspects in itâs reality. Physical and non-physical has itâs own important role as in this process. Development in urban areas is growing, especially in Gorontalo city commercial area to meet community needs for container activity by high economic growth. Development of a road corridor is not possible regardless of the activities that are inside. Variety of formal sector activity will be followed by the informal sector, which gives unique pattern on a road corridor. It also gives a different value when compared to other road corridors. The research provides an influence of physical setting and activities of street vendors to the linkage district. The research method used is qualitative rationalistic, with analytical techniques using place centered mapping and person centered mapping method combined with the time budget method. Place centered mapping is used to know the characteristics and the amount of space used PKL physical setting and to know the location of the nodes (area magnet). Person centered mapping is used to know the movement and circulation disorders pedestrians and motor vehicles which perform the movement in the streets. The results of this method, then do superimpose to know how to influence. The conclusions of this research indicates that the effect caused by the physical characteristics of street vendors setting of type 2, type 4, type 5 and type 7 is quite significant in raising the quality of the linkage, so the recommendation is directed to attempt to neutralize the excessive pressure on street space by changing the types of the problem with the type.